2023
DOI: 10.2147/ijgm.s395948
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Liver Fibrosis in Chinese Patients with Type 2 Diabetes Mellitus and Non-Alcoholic Fatty Liver Disease

Abstract: Purpose Non-alcoholic fatty liver disease (NAFLD) and type 2 diabetes mellitus (T2DM) are frequently co-occurring diseases. Liver fibrosis (LF), with increasing incidence, has a prognostic value for NAFLD mortality. Our study aimed to investigate the relevant factors for FL in T2DM individuals with NAFLD. Patients and Methods A total of 565 T2DM patients with NAFLD from Hebei General Hospital participated in the study. Patients underwent an abdominal ultrasound, a quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 59 publications
1
4
0
Order By: Relevance
“…Compared with normal patients, patients with diabetes have a higher risk of liver fibrosis. In addition, studies ( 33 , 34 ) have shown that serum AST is increased when liver injury occurs in patients with NAFLD, and it has been preliminarily confirmed that AST level is closely related to the occurrence of liver fibrosis in patients with NAFLD, which is highly similar to our findings. A previous study ( 35 ) showed that patients with advanced fibrosis (F3-F4) were older, more obese, more prone to diabetes and tened to have elevated levels of GGT compared to other groups, thus suggesting that GGT could be a biomarker for liver fibrosis in patients with NAFLD.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Compared with normal patients, patients with diabetes have a higher risk of liver fibrosis. In addition, studies ( 33 , 34 ) have shown that serum AST is increased when liver injury occurs in patients with NAFLD, and it has been preliminarily confirmed that AST level is closely related to the occurrence of liver fibrosis in patients with NAFLD, which is highly similar to our findings. A previous study ( 35 ) showed that patients with advanced fibrosis (F3-F4) were older, more obese, more prone to diabetes and tened to have elevated levels of GGT compared to other groups, thus suggesting that GGT could be a biomarker for liver fibrosis in patients with NAFLD.…”
Section: Discussionsupporting
confidence: 91%
“…Compared with normal patients, patients with diabetes have a higher risk of liver fibrosis. In addition, studies (33,34) have shown that serum AST is increased when liver injury occurs in patients with NAFLD, and it has been preliminarily A calculator for predicting significant fibrosis probability in patients with nonalcoholic fatty liver disease. confirmed that AST level is closely related to the occurrence of liver fibrosis in patients with NAFLD, which is highly similar to our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, patients who had been living with diabetes for more than five years exhibited elevated odds of developing liver fibrosis. A study conducted by Luo et al also demonstrated a positive correlation between diabetes duration and FIB-4 scores [20]. In line with this, a study conducted in Hong Kong revealed that liver-related events escalated linearly with the duration of diabetes [21].…”
Section: Discussionmentioning
confidence: 63%
“…The role of platelets in the inflammatory process in NAFLD is well known, as they are included in numerous scores that evaluate the process of non-invasive fibrosis. Thus, a study that included 565 patients with NAFLD and diabetes, and aimed to highlight the factors that are associated with liver fibrosis in these patients, showed a statistically significant (p < 0.01) higher average value of platelets in NAFLD without liver fibrosis patients (a mean value of 226.000/mmc, with limits of 211.000-279.000/mm 3 ) compared to those with NAFLD and liver fibrosis (a mean value of 201.000/mmc, with limits of 173.500-238.000/mmc) [54]. Related to the characteristics of platelets, in our study, the average value of PDW was higher in the group of patients with HS and T2DM, compared to the group of patients with NASH and T2DM.…”
Section: Discussionmentioning
confidence: 78%